1999
DOI: 10.1016/s0002-9270(99)00038-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of antiendomysium and antigliadin antibodies in untreated celiac disease: disappointing in clinical practice

Abstract: Interpretation of negative serology needs great awareness. Although EMA sensitivity in total villous atrophy is excellent, in partial villous atrophy the sensitivity of EMA appears to be disappointing. Our experience shows that EMA and AGA have only limited value in screening programs for CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
139
1
8

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 0 publications
5
139
1
8
Order By: Relevance
“…The histologic changes in biopsies from such patients are not sufficient to make the diagnosis of celiac disease according to the established criteria 37 and the interpretation of these biopsies is further compounded by the fact that serologic tests are often negative at this stage. 38,39 Mino and Lauwers, 13 presumably, also used a cutoff of 20 lymphocytes/ 100 epithelial cells for similar reasons. If we use 25 lymphocytes/100 epithelial cells as the upper limit of normal, an increased number of intraepithelial lymphocytes would still be seen in a substantial number (28%) of duodenal biopsies from patients with H. pylori gastritis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The histologic changes in biopsies from such patients are not sufficient to make the diagnosis of celiac disease according to the established criteria 37 and the interpretation of these biopsies is further compounded by the fact that serologic tests are often negative at this stage. 38,39 Mino and Lauwers, 13 presumably, also used a cutoff of 20 lymphocytes/ 100 epithelial cells for similar reasons. If we use 25 lymphocytes/100 epithelial cells as the upper limit of normal, an increased number of intraepithelial lymphocytes would still be seen in a substantial number (28%) of duodenal biopsies from patients with H. pylori gastritis (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…While serological screening remains a powerful tool in the diagnosis of CD, it has been demonstrated that EMA sensitivity is reduced in cases of partial rather than total villous atrophy (15), and the gold standard for the diagnosis of cluster of differentiation remains the finding of villous atrophy on duodenal biopsy.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The disease is characterized by lesions of the small intestine with partial to total villous atrophy, crypt hyperplasia and invasion of lymphocytes into the gut epithelium and lamina propria. 3,4 The main clinical symptoms include chronic diarrhoea and growth retardation, but abdominal pain, anaemia, osteopenia and chronic fatigue may also occur. 5 However, most patients show only some of these symptoms, while others are monosymptomatic or have no symptoms at all.…”
Section: Introductionmentioning
confidence: 99%